Synthesis of Novel FTY720 Analogs with Anticancer Activity through PP2A Activation - Jitendra Shrestha; Sung Hwan Ki; Sang Mi Shin; Seon Woong Kim; Joo-Youn Lee; Hee-Sook Jun; Taeho Lee; Sanghee Kim; Dong Jae Baek; Eun-Young Park (Molecules, 2018)
FTY720 inhibits various cancers through PP2A activation. The structure of FTY720 is also used as a basic structure for the design of sphingosine kinase (SK) inhibitors. We have synthesized derivatives using an amide chain in FTY720 with a phenyl backbone, and then compounds were screened by an MTT cell viability assay. The PP2A activity of compound 7 was examined. The phosphorylation levels of AKT and ERK, downstream targets of PP2A, in the presence of compound 7, were determined. Compound 7 may exhibit anticancer effects through PP2A activation rather than the mechanism by inhibition of SK1 in cancer cells. In the docking study of compound 7 and PP2A, the amide chain of compound 7 showed an interaction with Asn61 that was different from FTY720, which is expected to affect the activity of the compound.